Oospore dimensions and morphology in North American Tolypella (Charophyceae, Charophyta). Issue 2 (11th February 2015) - Pérez, William; Hall, John D.; McCourt, Richard M.; Karol, Kenneth G.; Vis, M.
<x xml:space="preserve">Abstract</x> Characteristics of the oospores have been used to delimit sections and, in some cases, species in the genus Tolypella A. Braun. To test the utility of oospore characters for identifying North American species of Tolypella, we investigated oospores from field‐collected and herbarium specimens. Oospore dimensions (length, width, and length to width ratio) and morphology (color, ridge number and shape, wall ornamentation, and basal impression number) were measured. Oospore dimensions were statistically analyzed and oospore morphology was studied with light and scanning electron microscopy. Statistical analyses showed significant differences in length, width, and length to width ratios among most Tolypella species and populations but there was considerable overlap, which suggested that species identification based on oospore measurements alone is not wholly reliable. In addition, oospore morphology was not unique for every species.